2020
DOI: 10.1002/bio.3785
|View full text |Cite
|
Sign up to set email alerts
|

Use of eosin for green spectroscopic determination of mebendazole

Abstract: New, sensitive, and reliable spectroscopic methods were constructed for the fast determination of the anthelmintic drug mebendazole. The methods depended on the reaction of the amino group in mebendazole with eosin in acidic medium forming an ion pair complex. The first method, Method I, relied on quenching of the native fluorescence of eosin after reaction with mebendazole at pH 3.7 using acetate buffer. Fluorescence quenching was measured at 538 nm after excitation at 518 nm. This method showed a linear resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Mechanisms of quenching involve either the interaction of the drug with EY through electron transfer, 26,27 or more commonly through ion-pair complexation between the drug and EY. [28][29][30] The use of EY as a sensing material has been demonstrated for the analysis of many drugs such as antibiotics, 31,32 beta-blockers, 28 and psychoactive drugs. 33 The advantages of using EY for the drug determination include high sensitivity, simplicity, cost effectiveness, and low detection limits.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms of quenching involve either the interaction of the drug with EY through electron transfer, 26,27 or more commonly through ion-pair complexation between the drug and EY. [28][29][30] The use of EY as a sensing material has been demonstrated for the analysis of many drugs such as antibiotics, 31,32 beta-blockers, 28 and psychoactive drugs. 33 The advantages of using EY for the drug determination include high sensitivity, simplicity, cost effectiveness, and low detection limits.…”
Section: Introductionmentioning
confidence: 99%
“…Different analytical methods have been reported in the literature for the estimation of mebendazole either in pure form and formulations. These include HPLC [3][4][5] , spectrophotometry [6][7][8][9][10][11] , liquid chromatography-mass spectroscopy 12 and fluorimetry 13 . Most of the reported spectrophotometric methods depend on the formation of complexes which need an extraction step to get the formed colored product.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the literature showed that several spectrophotometric methods have been reported for the determination of MBL in pharmaceutical doses and biological samples. Most of these methods rely on several interactions between MBL and reagents to create a spectroscopically estimated color product for MBL, of which: (Eosin) (9) , (AgNPs) (10) , (Methanolic Hydrochloride) (11) , (N-Chloro Succinamide) (12) , (DNSA and CA) (13) , (Lanthanum (III)) (14) , (H2SO4 in methanol) (15) , (1-fluoro 2,4-dinitrobenzene) (16) .…”
Section: Introductionmentioning
confidence: 99%